Hardware and computer organization : the software perspective - Berger, Arnold S. (Embedded technology series., 2005)
Hardware and Computer Organization is a practical introduction to the architecture of modern microprocessors for students and professional alike. It is designed to take practicing professionals under the hood of a PC and provide them with an understanding of the basics of the complex machine that has become such a pervasive part of our everyday life. It clearly explains how hardware and software cooperatively interact to accomplish real-world tasks. Instead of simply demonstrating how to design a computers hardware, it provides an understanding of the total machine, highlighting strengths and weaknesses, explaining how to deal with memory and how to write efficient assemble code that interacts with and takes best advantage of the underlying hardware. Additionally, the book has a unique emphasis on facilitating the ability to make real engineering decisions in industry when working with anything from simple 8-bit microprocessors in embedded applications to PCs and workstations. It demystifies the link between the behaviour of the code and the operation of the machine, while helping engineers and students to better understand the limitations imposed by finite speed and resources. This book is divided into three major sections: Part 1: Hardware Fundamentals and Digital Design Part 2: Assembly Language Programming Part 3: Computer Architecture The DVD accompanying the text will contain the following: *source code files for all the code examples used in the text *working demo versions of two different processor simulators *video lectures from industry notables covering several of the major topics dealt with in the text.